Vascular endothelial growth factor A promotes platelet adhesion to collagen IV and causes early brain injury after subarachnoid hemorrhage - Zun-Wei Liu (Neural Regeneration Research, 2019)
The role of vascular endothelial growth factor A in platelet adhesion in cerebral microvessels in the early stage of subarachnoid hemorrhage remains unclear. In this study, the endovascular puncture method was used to produce a rat model of subarachnoid hemorrhage. Then, 30 minutes later, vascular endothelial growth factor A antagonist anti-vascular endothelial growth factor receptor 2 antibody, 10 μg, was injected into the right ventricle. Immunohistochemistry and western blot assay were used to assess expression of vascular endothelial growth factor A, occludin and claudin-5. Immunohistochemical double labeling was conducted to examine co-expression of GP Ia-II integrin and type IV collagen. TUNEL was used to detect apoptosis in the hippocampus. Neurological score was used to assess behavioral performance. After subarachnoid hemorrhage, the expression of vascular endothelial growth factor A increased in the hippocampus, while occludin and claudin-5 expression levels decreased. Co-expression of GP Ia-II integrin and type IV collagen and the number of apoptotic cells increased, whereas behavioral performance was markedly impaired. After treatment with anti-vascular endothelial growth factor receptor 2 antibody, occludin and claudin-5 expression recovered, while co-expression of GP Ia-II integrin and type IV collagen and the number of apoptotic cells decreased. Furthermore, behavioral performance improved notably. Our findings suggest that increased vascular endothelial growth factor A levels promote platelet adhesion and contribute to early brain injury after subarachnoid hemorrhage. This study was approved by the Biomedical Ethics Committee, Medical College of Xi’an Jiaotong University, China in December 2015.